An exploratory study on using red mud waste as a replacement for fly ash to prepare Engineered Cementitious Composites. (1st August 2022) - Kan, Lili; Wang, Fei; Zhang, Yafeng; Wei, Yanping; Wu, Min
Abstract: This work tries to develop sustainable and high ductile materials with the use of red mud (RM) waste for applications which are challenging for normal brittle concretes. RM is a by-product from the alumina industry where huge amounts are generated every year. Stockpiled RM not only occupies vast areas of land but also imposes severe risks to the surrounding soil and groundwater. Civil engineering applications offer the possibilities for large volume utilization of RM. This work focuses on studying the properties of Engineered Cementitious Composites with RM as a replacement for fly ash (RM-ECCs). The results revealed that excellent tensile strain capacities can be achieved by all the studied mixes with different RM ratios and the maximum strain is up to 7.43%. Instead of negatively affecting mechanical properties, RM replacement with the ratios below 10% could improve both tensile and compressive strengths of the mixes. A Digital Image Correlation (DIC) technology was employed to allow effective real time observation of the whole cracking processes under loading. Analysis of the three-point bending and single crack tensile test results indicated that the high tensile ductility of the studied mixes can be explained by the determined meso-scale parameters. The results from SEM-EDS and FT-IR demonstrated that the reaction products are mainly silicate and aluminosilicate gels, and the inclusion of RM modifies the microstructure. Highlights: Red mud was recycled to develop sustainable and high ductile engineering materials. The maximum tensile strain capacity of the composite with red mud was up to 7.43%. Appropriate red mud replacement could improve the mechanical properties. A Digital Image Correlation technology was used to observe the cracking processes. Correspondence was found between the macro-, meso- and micro-scale properties.